The End of the Christian Life : How Embracing Our Mortality Frees Us to Truly Live - Billings, J. Todd (Grand Rapids, Michigan : Brazos Press, a division of Baker Publishing Group, 2020)
We're all going to die. Yet in our medically advanced, technological age, many of us see death as a distant reality--something that happens only at the end of a long life or to other people. In The End of the Christian Life, Todd Billings urges Christians to resist that view. Instead, he calls us to embrace our mortality in our daily life and faith. This is the journey of genuine discipleship, Billings says: following the crucified and resurrected Lord in a world of distraction and false hopes. Drawing on his experience as a professor and father living with incurable cancer, Billings offers a personal yet deeply theological account of the gospel's expansive hope for small, mortal creatures. Artfully weaving rich theology with powerful narrative, Billings writes for church leaders and laypeople alike. Whether we are young or old, reeling from loss or clinging to our own prosperity, this book challenges us to walk a strange but wondrous path: in the midst of joy and lament, to receive mortal limits as a gift, an opportunity to give ourselves over to the Lord of life.
Welcome to Sheol: A guided tour of life in the pit -- Two views of mortality: Is death an enemy or a friend? -- Mortals in denial: Living as dying creatures -- Interplanetary exploration: The strange new world of modern medicine -- The way of prosperity and the Christian way -- The fracturing of our stories, and life after death -- Hoping for the end as mortals -- Conclusion.
Includes bibliographical references and indexes.
Keywords: Death -- Religious aspects -- Christianity; Death -- Biblical teaching; Resurrection -- Biblical teaching; Hope - Biblical Teachings -- Religious aspects -- Christianity; Christian life -- Reformed authors; Christian Morality